2013
DOI: 10.1037/a0033761
|View full text |Cite
|
Sign up to set email alerts
|

The 5-HTTLPR polymorphism in the serotonin transporter gene moderates the association between emotional behavior and changes in marital satisfaction over time.

Abstract: Why do some individuals become dissatisfied with their marriages when levels of negative emotion are high and levels of positive emotions are low, whereas others remain unaffected? Using data from a 13-year longitudinal study of middle-aged and older adults in long-term marriages, we examined whether the 5-HTTLPR polymorphism in the serotonin transporter gene moderates the association between negative and positive emotional behavior (objectively measured during marital conflict) and changes in marital satisfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 77 publications
(134 reference statements)
5
37
0
Order By: Relevance
“…Specifically, in this aggregate analysis, individuals’ 5-HTTLPR genotype explained about 2% of variance in positive emotional expressions. This is consistent with the idea that these kinds of genetic influences do not determine individuals’ emotional reactivity (Haase et al, 2013). Rather, candidate genes such as 5-HTTLPR represent one small source of individual differences in positive emotional expressions, alongside other sources such as age (Carstensen et al, 1995), gender (LaFrance, Hecht, & Paluck, 2003), culture (Ekman & Friesen, 1969), depressive symptomatology (Tremeau et al, 2005), and other genetic influences (Pelc, Cheron, & Dan, 2008).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Specifically, in this aggregate analysis, individuals’ 5-HTTLPR genotype explained about 2% of variance in positive emotional expressions. This is consistent with the idea that these kinds of genetic influences do not determine individuals’ emotional reactivity (Haase et al, 2013). Rather, candidate genes such as 5-HTTLPR represent one small source of individual differences in positive emotional expressions, alongside other sources such as age (Carstensen et al, 1995), gender (LaFrance, Hecht, & Paluck, 2003), culture (Ekman & Friesen, 1969), depressive symptomatology (Tremeau et al, 2005), and other genetic influences (Pelc, Cheron, & Dan, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…Study 3 examined middle-aged and older spouses discussing an area of disagreement in their marriage. Our choice to probe positive emotional expressions in a marital conflict discussion was based on a large body of research showing that (genuine) positive emotions do occur in the midst of negative experiences (Folkman & Moskowitz, 2000; Papa & Bonanno, 2008) including marital conflict discussions (Carstensen, Gottman, & Levenson, 1995; Haase et al, 2013). Positive emotions serve important functions in negative contexts, including physiological soothing (Yuan, McCarthy, Holley, & Levenson, 2010) and “undoing” the cardiovascular effects of negative emotions (Fredrickson & Levenson, 1998; Fredrickson, Mancuso, Branigan, & Tugade, 2000).…”
Section: The Present Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, the marital satisfaction of 5- HTTLPR s allele carriers demonstrated greater response to both positive and negative marital context. Likewise, Haase et al (2013) found that the marital satisfaction of individuals who were 5- HTTLPR s allele carriers were more strongly and negatively influenced by the presence of negative emotion and more strongly positively affected by the presence of positive emotion. Taken together, then, there appear to be effects of stressors on relationship satisfaction, of relationship satisfaction on stressors, and of stressors on physiological stress, with the potential for these effects to be amplified by variation at 5- HTTLPR .…”
mentioning
confidence: 92%
“…62 Similarly, long or short variants of a serotonin transporter gene impact marital satisfaction, which likely may play an indirect role in mating choices. 63 …”
Section: Individual Variables Influencing Mating Strategy Preferencementioning
confidence: 99%